Innovate, Fund, Thrive The Entrepreneur's Playbook to VC Fundraising in Life Sciences. - Denault, Jean-Francois (Productivity Press, 2024)
Entrepreneurs in life sciences face a unique set of challenges when raising funds. These encompass fundamental issues like navigating R&D risks and crafting a robust commercialization strategy, extending to more challenging hurdles like adeptly handling intellectual property issues, overseeing the regulatory development and approval processes, as well as coordinating extended and expensive phases of research and development. The authors present this book in two parts. In the first part, the focus is on getting ready to meet potential partners and investors and includes topics such as identifying the information organizations and start-ups need, collecting and collating that information, and building a compelling story. The second part provides a deep dive into the investor's perspective, offering insights into how proposals are evaluated, along with an exclusive glimpse into the due diligence journey. Additionally, the book reveals "Eight Classic Mistakes Life Science Entrepreneurs Make", offering valuable insights and lessons gained from the authors' experiences. Although the book is divided into two parts, it maintains an interconnected approach. Both authors contribute insights based on their professional and personal experiences, offering feedback and perspectives throughout the book. Philippe provides his investor's perspective on the preparation steps, while Jean-Franois shares his insights as an experienced entrepreneur, coach, and mentor. This collaborative approach enhances the depth and practicality of the guidance provided. Discover the art of preparing a compelling pitch, igniting excitement, and embarking on your path to fundraising success!
Description based upon print version of record.
7.2. Presenting Qualitative Data
Keywords: Fund raising.; elektronické knihy; electronic books